Source identification of ultrafine particulate matter and ammonia emissions in the metropolitan area - Heo, Jaeseok; Kim, Pilho; Park, Jongsung; Lee, Jae Young (Environmental Engineering Research, 2025)
Previous studies have estimated the sources of particulate matter in the atmosphere. Among these, studying the sources of secondary aerosols harmful to human health is important. However, there is a lack of research on ammonia (NH3), a precursor to secondary aerosol formation. This study uses positive matrix factorization (PMF) model and conditional bivariate probability function (CBPF) model to estimate the sources of particulate matter and ammonia. The results showed that about 40% of the PM2.5 mass at both sites was attributable to secondary aerosol. To estimate the emission sources of ammonia that contribute to the generation of secondary aerosols, CBPF was utilized to model and compare the emission characteristics of categorized pollution sources and ammonia, and it was found that SMA had similar emission trends to industry, road dust, oil combustion, and biomass combustion, while GRA had similar emission trends to oil combustion and vehicle (diesel). Considering the results from these two regions, ammonia in the metropolitan area is more likely to be emitted from daily activities than from long distances. The study results demonstrate the major role of secondary aerosols on ambient PM2.5 concentrations and can help develop effective management strategies and policies for air pollution mitigation.
Keywords: Bivariate; Emission; Environment monitoring; Metropolitan area; Particular matter; Particulate Matter; PM 2.5; Positive Matrix Factorization; Probability functions; Secondary aerosols; Ammonia; Emissions; Environment monitoring; Particular matter; PMF